Mechanical properties and superficial characterization of a milled CAD-CAM glass fiber post. (June 2018) - Ruschel, George Hebert; Gomes, Érica Alves; Silva-Sousa, Yara Terezinha; Pinelli, Rafaela Giedra Pirondi; Sousa-Neto, Manoel Damião; Pereira, Gabriel Kalil Rocha; Spazzin, Aloísio Oro
Abstract: Computer-aided design and computer-aided manufacturing (CAD-CAM) technology may be used to produce custom intraradicular posts, but studies are lacking. The purpose of this in vitro study was to evaluate the flexural properties (strength and modulus), failure mode, superficial morphology, and roughness of two CAD-CAM glass fiber posts (milled at different angulations) compared with a commercially available prefabricated glass fiber post. Three groups were tested (n = 10): PF (control group)– prefabricated glass fiber post; C-Cd–diagonally milled post; and C-Cv–vertically milled post. A 3-dimensional virtual image was obtained from a prefabricated post, which guided the posterior milling of posts from a glass fiber disk (Trilor Blanks; Bioloren). Surface roughness and morphology were evaluated using confocal laser microscopy. Flexural strength and modulus were evaluated with the 3-point bend test. Data were submitted to one-way analysis of variance followed by the Student-Newman-Keuls post hoc test (α = 0.05). The fractured surfaces were evaluated with scanning electron microscopy. The superficial roughness was highest for PF and similar for the experimental groups. Morphological analysis shows different sizes and directions of the glass fibers along the post. The flexural strength was highest for PF (900.1 ± 30.4 > C-Cd − 357.2 ± 30.7 > C-Cv 101.8 ± 4.3 MPa) as was the flexural modulus (PF 19.3 ± 2.0 GPa > C-Cv 10.1 ± 1.9 GPa > C-Cd 7.8 ± 1.3 GPa). A CAD-CAM milled post seems a promising development, but processing requires optimizing, as the prefabricated post still shows better mechanical properties and superficial characteristics.